Prevalencia de Eimeria sp y estudio morfométrico de ooquistes hallados en canes domésticos de Perú. - Torrel Pajares, T. (2022)
Eimeriosis is a disease caused by a protozoan of the genus Eimeria that affects all wild and domestic animals. Given that there are no previous reports in Peru and in other regions of Latin America, the prevalence is null or low in domestic dogs, the objective of this work was to determine the prevalence of Eimeria sp in dogs from the city of Cajamarca through coproparasitological analysis, using the Faust method and making the morphometric study of the oocysts. It obtained 206 fecal samples randomly in the east area of Cajamarca and were immediately processed at Laboratorio de Parasitología Veterinaria de la Universidad Nacional de Cajamarca, Perú. The prevalence found was 10.68% for Eimeria sp in domestic dogs. To the morphometric study of the oocysts, measurements of length and width were determined; these presenting an average of 21.73 pm long and 17.77 pm wide for the ovoid shape; 16.40 pm long and 15.31 pm wide for the spherical shape, finally 25.54 and 18.51 pm respectively for the ellipsoidal shape. These results prove the presence and mild infection by Eimeria sp in domestic dogs in the northern highlands of Peru, also suggesting future studies of the protozoan to avoid risks or conditions to public health.